2022
DOI: 10.1002/ijgo.14185
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results on transmission of SARS‐CoV‐2 antibodies to the fetus and serum neutralizing activity

Abstract: During pregnancy early third trimester immunization against SARS‐CoV‐2 confers optimal immunity to the neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Evidence of efficient placental SARS-CoV-2 antibodies transfer had been previously demonstrated 25 , 28 , but uncertainties remained regarding the impact of maternal disease severity and the delay required to obtain efficient transfer. Similarly to others, we observed that the placental antibody transfer was proportional to time elapsed since maternal infection 27 31 , 36 38 . Indeed, Brebant et al .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Evidence of efficient placental SARS-CoV-2 antibodies transfer had been previously demonstrated 25 , 28 , but uncertainties remained regarding the impact of maternal disease severity and the delay required to obtain efficient transfer. Similarly to others, we observed that the placental antibody transfer was proportional to time elapsed since maternal infection 27 31 , 36 38 . Indeed, Brebant et al .…”
Section: Discussionsupporting
confidence: 88%
“…Although, Flannery et al . 26 detected specific IgG in 86.7% (72/83) of exposed fetuses, information regarding the potential impact of the delay between maternal infection and delivery regarding materno-fetal antibody transfer is still being explored 27 31 . Due to the significant protection offered by passive immunization acquired through maternal antibodies to the vulnerable newborn and its potential impact on vaccination campaigns, comparing the efficiency of placental antibody transfer in the first, second, and third trimester of infection with SARS-CoV-2 needs to continue to be explored.…”
Section: Introductionmentioning
confidence: 99%